The Effectiveness of Articulate Storyline 3 Application-Based Interactive Learning Media in Social Studies Learning for Elementary School - Nursalam Nursalam; Muhajir Muhajir; Slamet Aji Wibowo; Suardi Suardi (AL-ISHLAH: Jurnal Pendidikan, 2023)
The research problem is students' low reading skills and social studies learning outcomes. This research aims to apply interactive media Articulate Storyline 3 to improve students' general map reading skills and learning outcomes in elementary school subjects in Makassar City. This study uses the ASSURE Research and Development (RD) research method (Analyze Learner Characteristics, State Objective Select Media, Utilize Media, Required learner participation Evaluate and revise) to develop learning media that can improve reading skills and learning outcomes for 28 elementary school students in Makassar city. The results showed that interactive learning media was declared effective because two indicators were achieved: the observations of student activities included in the very active category and the observations of teacher activities included in the very active category. Implications in learning can improve skills and student learning outcomes.